Acceptance of large corporate receivables as collateral – the practice of the Magyar Nemzeti Bank in view of the principles of collateral management, with a specific focus on legal risks - Lerner-Nagy, Dániel; Straubinger, András; Szabadkai, Dániel (Public Finance Quarterly, 2023)
In the spring of 2020, the Magyar Nemzeti Bank (MNB) expanded the pool of assets eligible as collateral for central bank lending by accepting loans granted to large corporates customers as collateral, thus widening the lending channel between the MNB and credit institutions and providing credit institutions with a wider leeway in ALM (Asset-Liability Management). In this paper we analyse the MNB’s framework of conditions for the eligibility of large corporate receivables in respect to the principles of collateral management including, in particular, the management of legal risks. The inclusion of such transactions as collateral is challenging from both a legal and an operational perspective, since eligibility for use as collateral requires the development of a framework that fully ensures the enforceability of large corporate receivables accepted as collateral, and compliance with all other relevant collateral management principles. It is concluded from the analysis that a set of strict conditions and the operational framework supporting it can ensure the management of legal risks, but can also be noted that there may be trade-offs between simple asset-liability and liquidity management, and compliance with the complex system of corporate receivables conditions.